Microcelebrity around the globe - Abidin, Crystal; Brown, Megan Lindsay (Emerald Publishing Limited, 2018)
This absorbing anthology uses in-depth interdisciplinary case studies from across the globe to examine the practice and concept of microcelebrity. Expanding on the existing theoretical framing of the online celebrity experience, the editors re-theorize microcelebrity to accommodate developments in global internet governance, the evolution of platform politics, the emergence of hybrid forms of celebrity, and the collapsing networks between old and new media. Chapters analyse experiences across Asia, Europe, Latin America and Australia, and consider microcelebrities at all stages of their careers, from everyday users and beginners to veteran influencers.Arguing for new perspectives and theories of microcelebrity that take into account colonial geographies, cross-media networks between influencers and legacy media, and gendered aggression and political discourses in a social media-saturated age, this volume will be of huge value to students and scholars of microcelebrity, social media, digital labour, creative industries and internet culture.
Includes index.
Keywords: Online social networks.; Social Science -- Popular Culture.; Popular culture.; elektronické knihy; electronic books